2023
DOI: 10.1186/s12888-023-05438-9
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting depression and COVID-19: a cohort study on the risk of susceptibility and hospitalization

Nastaran Nasirpour,
Neda Esmailzadehha,
Ahmad Hajebi
et al.

Abstract: Background Depression can have negative effects on a person’s physical health. However, the available evidence on the risk of susceptibility to COVID-19 and its adverse outcomes in people with mental disorders, including depression, is limited and inconsistent. Therefore, we investigated the relationship between major depressive disorder (MDD) and the risk of susceptibility to COVID-19 infection and hospitalization. The data used in the study were obtained from the Employees’ Health Cohort Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…7 A cohort study demonstrated that susceptibility to COVID-19 infection had significantly higher risk in individuals with depressive disorder than those without it. 8 Ethnicity is possible to be involved in susceptibility to COVID-19 infection. Black ethnic population shows more susceptible to risk factor for COVID-19 infection in Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 A cohort study demonstrated that susceptibility to COVID-19 infection had significantly higher risk in individuals with depressive disorder than those without it. 8 Ethnicity is possible to be involved in susceptibility to COVID-19 infection. Black ethnic population shows more susceptible to risk factor for COVID-19 infection in Japanese patients.…”
Section: Introductionmentioning
confidence: 99%